2017
DOI: 10.3344/kjp.2017.30.4.258
|View full text |Cite
|
Sign up to set email alerts
|

The effects of regular exercise on capsaicin-induced pulpal pain and pain-induced changes in passive avoidance learning and memory in rats

Abstract: BackgroundPulpal pain is one of the most common and severe orofacial pain conditions with considerable adverse effects on physiological processes including learning and memory. Regular exercise is known to be effective on cognitive function as well as pain processing in the central nervous system. Here, the possible effects of regular exercise on pulpal pain response as well as pain-induced changes in learning and memory efficiency in rats were investigated.MethodsTwenty-four male Wistar rats were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These findings are consistent with previous studies showing that treadmill running exerts fewer preventive effects to reduce nocifensive responses in neuropathic pain models [14,69,78]. In contrast, daily exercise for several weeks before acute tooth pulp stimulation decreases orofacial nocifensive behaviors [41]. These discrepancies are likely due to the differences in pain models and treadmill running protocols, and our treadmill running protocol (10 m/min, 30 min, 10 days) was not sufficient to behaviorally decrease masseter muscle nociception in non-SDS mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous studies showing that treadmill running exerts fewer preventive effects to reduce nocifensive responses in neuropathic pain models [14,69,78]. In contrast, daily exercise for several weeks before acute tooth pulp stimulation decreases orofacial nocifensive behaviors [41]. These discrepancies are likely due to the differences in pain models and treadmill running protocols, and our treadmill running protocol (10 m/min, 30 min, 10 days) was not sufficient to behaviorally decrease masseter muscle nociception in non-SDS mice.…”
Section: Discussionsupporting
confidence: 92%
“…The second aim of this study was to determine the role of physical exercise in masseter muscle nociception, as indicated by orofacial nocifensive behaviors in SDS-susceptible mice. A few studies have demonstrated that exercise decreases orofacial nociception in models of tooth pulp [41] and infraorbital nerve injury pain [42]; however, there is a lack of evidence on the effect of exercise on deep craniofacial nociception. This study employed a treadmill running paradigm because parameters such as duration and intensity could be accurately controlled.…”
mentioning
confidence: 99%
“…2 ). The sample size and number of animal per groups were designated according to the pilot experiments and previous studies in the field in our lab [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dose of drugs and the number of animal per group were determined from previous studies [ 15 17 ]. Besides, our previous study indicated that intra-Vc administration of orexin-A vehicle, distilled water, and DMSO as a vehicle of OX1Rs antagonist (SB-334867-A) had no effect on the strictness of capsaicin-induced orofacial pain.…”
Section: Methodsmentioning
confidence: 99%